The Neuropeptides Vasoactive Intestinal Peptide and Pituitary Adenylate Cyclase-Activating Polypeptide Control HIV-1 Infection in Macrophages Through Activation of Protein Kinases A and C - Temerozo, Jairo R.; de Azevedo, Suwellen S. D.; Insuela, Daniella B. R.; Vieira, Rhaíssa C.; Ferreira, Pedro L. C.; Carvalho, Vinícius F.; Bello, Gonzalo; Bou-Habib, Dumith Chequer (Frontiers in Immunology, 2018)
VIP and PACAP are highly similar neuropeptides present in several tissues, endowed with immunoregulatory functions and other systemic effects. We previously reported that both neuropeptides reduce viral production in HIV-1-infected primary macrophages, with the participation of β-chemokines and IL-10, and now we describe molecular mechanisms engaged in this activity. Macrophages exposed to VIP or PACAP before HIV-1 infection showed resistance to viral replication, comparable to that observed when the cells were treated after infection. Also, multiple treatments with a sub-optimal dose of VIP or PACAP after macrophage infection resulted in a decline of virus production similar to the inhibition promoted by a single exposure to the optimal inhibitory concentration. Cellular signaling pathways involving cAMP production and activation of protein kinases A and C were critical components of the VIP and PACAP anti-HIV-1 effects. Analysis of the transcription factors and the transcriptional/cell cycle regulators showed that VIP and PACAP induced CREB activation, inhibited NF-kB and reduced Cyclin D1 levels in HIV-1 infected cells. Remarkably, VIP and PACAP promoted G-to-A mutations in the HIV-1 provirus, matching those derived from the activity of the APOBEC family of viral restriction factors, and reduced viral infectivity. In conclusion, our findings strengthen the antiretroviral potential of VIP and PACAP and point to new therapeutic approaches to control the progression of HIV-1 infection.